Corporate taxpayers’ compliance variables under the self-assessment system in Malaysia : a mixed methods approach - Mohd Isa, Khadijah (Curtin University, 2012)
This thesis examines corporate taxpayers’ compliance variables and analyses the influence of business characteristics on compliance behaviour. A two-phase exploratory mixed methods approach was employed to explore participants’ views of corporate taxpayers’ compliance variables, with the intention of using this information to develop a survey instrument. The method comprised eight focus group interviews with 60 tax auditors from the Inland Revenue Board of Malaysia (IRBM), and a mixed-mode survey among selected Malaysian corporate taxpayers. Thematic analysis and descriptive and inferential analysis were mainly used to examine the qualitative and quantitative data.The results suggest that the main corporate taxpayers’ compliance variables are: tax knowledge, tax complexity, tax agents and tax audits. The main business characteristics that are found to have significant influence on compliance variables are the length of time the business has been operational, size and industry. Continuous tax education and tax audit programmes are thus vital, and should focus more closely on specific groups of taxpayers, namely smaller and more newly established companies, companies in rural areas, and business industries that are more inclined to use cash transactions. Moreover, as many corporate taxpayers perceive the probability of an audit as low, the IRBM should publicise its audit activities more prolifically through available media channels. Tax simplification, especially on laws regarding estimation of income tax, is also an important consideration.This study extends the scope of tax compliance research to corporate taxpayers, and builds upon the limited international and Malaysian literature in this area. Most of the research findings of this thesis yield consistent results with respect to particular tax compliance variables. In a tax policy context, this study enables international tax authorities in general, and Malaysian tax authorities in particular, to have greater confidence in developing and administering tax laws and policies to maintain and/or increase the overall level of corporate compliance.